Cognitive Factors Affecting Suicidal Ideation : A Preliminary Study - Mohamad Azhari, Abu Bakar; Rizal, Abu Bakar; Tan, Yao Xiong (Lembaga Kaunselor (Malaysia), 2019)
Suicidal ideation or suicidal thought is troubling but yet common. Suicidal ideation is basically thought about and planning suicide. This paper examined cognitive factors affecting suicidal ideation and attempted to put forward a model of suicidal ideation. The findings indicated that cognitive distortion, hopelessness, problem solving, and psychache are the common cognitive factors contributing to the development of suicidal ideation. However, the findings among previous studies are inconsistent. Other studies showed that rumination is the additional antecedent for suicidal thought. Preliminary results indicated a revised version of suicidal ideation model in understanding the nature of suicidal ideation, which includes cognitive distortion, hopelessness, problem solving, psychache, and rumination. This paper also disc future study.